Acceleration-feedback-based finite-time platoon control for interconnected vehicular system. (July 2022) - Zheng, Xinquan; Luo, Xiaoyuan; Wang, Jianmei; Yan, Jing; Guan, Xinping
Abstract: The platoon control problem of interconnected vehicular systems is investigated in this paper studies. A finite-time adaptive sliding mode control (SMC) method based on acceleration feedback is developed to achieve platooning of interconnected vehicular systems subject to external disturbances and string stability of the closed-loop platoon system is analyzed. The string stability of the closed-loop system is achieved by applying the constant spacing (CS) strategy in the proposed adaptive sliding mode controller under zero initial steady-state error conditions. A novel error definition method is proposed to transform the non-zero initial steady-state error into the zero initial steady-state error so that the proposed algorithm can be independent of the initial steady-state errors and reduce the large transient response caused by non-zero initial steady-state errors. The salient feature of the proposed SMC law is that it does not need to know the disturbance boundary in advance. Finally, simulations and experiments are conducted to demonstrate the advantages and effectiveness of the proposed algorithm. Graphical abstract: Highlights: The string stability can be guaranteed in any initial state. Acceleration feedback-based controller shows better transient performance. The finite-time control method improves the closed-loop system convergence rate. The proposed platoon control method provides guidance for practical systems.